2022
DOI: 10.1098/rsif.2022.0033
|View full text |Cite
|
Sign up to set email alerts
|

Large-scale mRNA translation and the intricate effects of competition for the finite pool of ribosomes

Abstract: We present a new theoretical framework for large-scale mRNA translation using a network of models called the ribosome flow model with Langmuir kinetics (RFMLK), interconnected via a pool of free ribosomes. The input to each RFMLK depends on the pool density, and it affects the initiation rate and potentially also the internal ribosome entry rates along each RFMLK. Ribosomes that detach from an RFMLK owing to termination or premature drop-off are fed back into the pool. We prove that the network always converge… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

4
4

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 57 publications
1
12
0
Order By: Relevance
“…Several mathematical models for the translation process have been described, and they include the TASEP model, the Ribosome Flow Model (RFM) and their variants 45,46,[64][65][66][67] . Totally Asymmetric Simple Exclusion Process or TASEP model assumes that an mRNA molecule is a one-dimensional lattice through which a ribosome can hop in only one direction from one site to the next, provided the latter is empty.…”
Section: Mathematical Model Of Translation At Single Mrna Level For C...mentioning
confidence: 99%
“…Several mathematical models for the translation process have been described, and they include the TASEP model, the Ribosome Flow Model (RFM) and their variants 45,46,[64][65][66][67] . Totally Asymmetric Simple Exclusion Process or TASEP model assumes that an mRNA molecule is a one-dimensional lattice through which a ribosome can hop in only one direction from one site to the next, provided the latter is empty.…”
Section: Mathematical Model Of Translation At Single Mrna Level For C...mentioning
confidence: 99%
“…This proves (20). To prove (21), consider first the case where the number of RFMIOs m is fixed and the total density in the network satisfies s → 0. Recall that q = e z /s, and (19)…”
Section: Proof Of Propositionmentioning
confidence: 99%
“…A generalization of this network, that includes the possibility of ribosome drop-off and attachment at each site along the RFM, was recently suggested in [21]. Simulations of this model showed that ribosome drop-off from an isolated mRNA always decreases the protein production rate, yet in the network ribosome drop-off from a jammed mRNA may increase the total production rate of all the mRNAs, as the drop-off frees ribosomes that enter the pool, and this improves the production rate in the other mRNAs.…”
Section: Introductionmentioning
confidence: 99%
“…A generalization of this network, that includes the possibility of ribosome drop-off and attachment at each site along the RFM, was recently suggested in [ 39 ]. Simulations of this model showed that ribosome drop-off from an isolated mRNA always decreases the protein production rate, yet in the network ribosome drop-off from a jammed mRNA may increase the total production rate of all the mRNAs, as the drop-off frees ribosomes that enter the pool, and this improves the production rate in the other mRNAs.…”
Section: Introductionmentioning
confidence: 99%